Implementation of Leadership by the Head of the Madrasah to Improve Employee Performance at Madrasah Aliyah Negeri 2 Majalengka - Yeti Kuswati; Herdianto Wahyu Pratomo; Arief Rahman Afief (Formosa Journal of Social Sciences (FJSS), 2024)
As an educational institution, the school has a role in managing and organizing intellectual education, spirituality, and skills to form and develop human resources with knowledge and skills based on faith and piety. To realize this goal, it is necessary to have good leadership from the head of the Madrasah and high performance from employees. Based on the research results conducted at Madrasah Aliyah Negeri 2 Majalengka, the implementation of leadership by the head of the Madrasah achieved a value of 60%. As for the performance of employees, they achieved a value of 59.6%, of which both received the title “Good enough”. Thus it can be concluded that the implementation of leadership conducted by the head of the Madrasah based on the application of leadership techniques has a parallel relationship with employee performance, so it has been tested and acceptable